Alelopatia e bioprospecção de Rapanea ferruginea e de Rapanea umbellata - Novaes, Paula (Universidade Federal de São Carlos, 2011)
Allelopathy is a process that involves primary or secondary metabolites produced by plants and microorganisms, which influences the growth and development of agricultural and biological systems. The intensity of plant allelopathic effects may depend on the hábitat, age and the biotic and abiotic conditions during the seasons in which they were collected. When allelopathic substances are purified and identified, they can be used to develop alternative products based on natural compounds to control weed species. The Brazilian savanna (cerrado) has very stressful environment conditions, mainly in dry periods, and should favor a greater variety of allelochemicals in Rapanea ferruginea (Ruiz & Pav.) Mez and Rapanea umbellata (Mart.) Mez (Primulaceae), which have leaves with resin canals and minute secretory glands, sparse throughout the abaxial surface, that can accumulate terpenes or tannins. This thesis hypothesis is that there must be allelopathic substances in the species of Rapanea to favor their establishment in the savanna and that they should be influenced by seasonal factors or by plant age. Allelopathy occurs by the release of allelochemicals in the environment and these may have economic importance, serving as molecular models for the production of natural herbicides, less harmful to the environment. In the first chapter, we compared the effect of plant age and season of leave collection on the allelopathic activity of aqueous extracts of R. ferruginea and R. umbelata. For this, germination and initial length bioassays were conducted using commercially bioindicator cultivated species (lettuce, tomato and onion) under the influence of the aqueous leaf extracts of adults and young individuals from wet and dry season at 10 and 5% (weight of leaf powder per volume of distilled water, g/mL). The extract of adult R. umbellata collected in the dry season showed the highest allelopathic activity and was chosen for the other studies of this thesis. In the second chapter, we compared the allelopathic activity of leaf aqueous extract of R. umbellata (10 and 5%) with the synthetic herbicide Oxyfluorfen on germination and initial length of weed species: barnyardgrass (Echinochloa crus-galli L., Poaceae), wild poinsettia (Euphorbia heterophylla L., Euphorbiaceae) and morning-glory (Ipomoea grandifolia Drammer., Convolvulaceae). In the third chapter, bioprospection, purification and isolation of secondary metabolites of agronomic interest was performed with R. umbellata leaves. Bioassays wheat of etiolated coleoptiles and germination and initial length of cress, lettuce, onion and tomato were performed under the effect of extracts of organic solvents for the direction of the compounds purification. The acetone extract was the most active and therefore was used to be fractionated by chromatographic column. It fractions were purified HPLC and Sephadex column. The isolated and purified compounds were identified by NMR1H and 13C spectra. This thesis results permit we to affirm that allelopathy is one way of the R. ferruginea and R. umbellata species to establish themselves in the savanna. The allelopathic activity of its leaves is influenced to a greater degree by the collection season (most active in dry season) than by plant age. The R. umbellata aqueous leaf extract showed distinct action than the Oxyfluorfen synthetic herbicide, being very active on the root part of the weed species while the synthetic herbicide was more active on the arial parts of these species. The bioprospection of R. umbellata leaves conditioned isolation and purification of the substances lutein and (-)- catechin. (-)-Catechin has the potential to be used as a natural origin and biodegradable herbicide.
Keywords: Alelopatia; Fitoquímica; Herbicida; Metabolitos secundários; Cerrado; Allelochemicals; Herbicide; Phytochemistry secondary metabolites; Savanna; CIENCIAS BIOLOGICAS::ECOLOGIA